Análise do Fluxo Reverso dos Bens de Pós-Consumo em uma Indústria de Beneficiamento de Coco: Desenvolvimento de uma Método Sustentável - Frota, Roberta Ramos (2010)
Excessive consumption and pressure to produce more and more have made a lot of waste to pile outside of the industries. Controlling the harm that all this waste has caused to the environment has become one of the current challenges. It has talked about waste because recognize the concern about the environmental question is not restricted to a segment of industrial activity or specific locations, but to an embracing and global attitude. It is the first step to face the challenge of the search for survival and adaptation to the new paradigms presented to the organizations. Therefore Reverse Logistics (RL) has been seen as a tool to be transformed into programs that result in gain for companies, consumers and society. So we have the following question: How to define an efficient method of application of reverse logistics in the process of coconut processing, involving the management of interorganizational skills to a better waste disposal? This scientific study will be based on methodological procedures appropriately structured, addressing the concepts and phenomena coherently and consistently. Thereby, data and information will be obtained through a bibliographic search, where researches were done in books, theses, newspapers, articles and more, and through field research where a study of the current situation of the company was made through local visits and meetings about the subject. Thus, this study came from the need to define a method of reverse logistics to contribute to an effective use of tools related to environmental management and sustainability. The development of this method helps in the process of deploying tools linked to reverse logistics, considering the people who are part of that company as essential agents of changes, besides trying to identify some interorganizational skills that should be developed for the company insert into its daily a new work routine.